2015
DOI: 10.1371/journal.pone.0132233
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographics, Comorbidities, Healthcare Utilization and Work Productivity in Japanese Patients with Adult ADHD

Abstract: ObjectivesThis study compared the sociodemographic characteristics, comorbidities, healthcare resource utilization, and work productivity among Japanese adults who reported being diagnosed with attention-deficit/hyperactivity disorder (ADHD) to those of a non-ADHD control population.MethodsData for this study were captured from an online survey of adults in Japan conducted by Kantar Health using consumer panels. A total of 84 survey participants reported they had received a diagnosis of ADHD from a physician. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 15 publications
5
35
0
2
Order By: Relevance
“…Individuals with ADHD also experience neuropsychological difficulties associated with deficient inhibition [ 22 ], memory [ 22 ], executive functioning [ 23 , 24 ], decision making [ 25 ], and emotional dysregulation [ 26 ]. Adult ADHD can have negative consequences for individuals’ self-esteem and the quality of interpersonal relationships, with both colleagues and significant others [ 27 , 28 ]. For example, in a community sample of 1001 adults, those with ADHD were significantly more likely to have been divorced (28% vs 15% controls, P ≤ 0.001) and were significantly less satisfied with their personal, social and professional lives [ 29 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with ADHD also experience neuropsychological difficulties associated with deficient inhibition [ 22 ], memory [ 22 ], executive functioning [ 23 , 24 ], decision making [ 25 ], and emotional dysregulation [ 26 ]. Adult ADHD can have negative consequences for individuals’ self-esteem and the quality of interpersonal relationships, with both colleagues and significant others [ 27 , 28 ]. For example, in a community sample of 1001 adults, those with ADHD were significantly more likely to have been divorced (28% vs 15% controls, P ≤ 0.001) and were significantly less satisfied with their personal, social and professional lives [ 29 ].…”
Section: Main Textmentioning
confidence: 99%
“…Adult ADHD has been associated with poorer driving and a higher incidence of traffic citations and motor vehicle accidents [ 35 ]. A recent study found that Japanese adults with ADHD visited physicians 10 times more often than a non-ADHD control group, and had rates of emergency room visits and hospitalization three times greater than controls [ 28 ]. Individuals with ADHD in Denmark have a lower life expectancy and more than double the risk of death than adults without ADHD [ 36 ].…”
Section: Main Textmentioning
confidence: 99%
“…The ICD-9 codes that are included in the clinical classification software (CCS) diagnosis of attention-deficit, conduct, and disruptive behavior disorders are shown in Table S1 (data not shown) along with a translation to respective codes in the Diagnostic and Statistical Manual for Mental Disorders IV, Text Revision. Importantly, since children and adults with ADHD have significantly higher rates of healthcare utilization [35][36][37] (including hospitalizations), hospital discharge diagnoses may be an important discriminatory marker of ADHD in diverse populations, potentially screening out "pure" or less severe ADHD, which are said to be a minority of cases [37] and even "highly atypical" [38]. It was our goal to test whether herbicide use predicts healthcare utilization for ADHD (i.e., likely significant ADHD impairment).…”
Section: Hospitalization Datamentioning
confidence: 99%
“…We were not seeking to establish or utilize state-based prevalence of ADHD, as community prevalence rates employ differing methodologies and would, therefore, be unreliable [39]. To control for the central nervous system comorbidities that are often associated with an ADHD diagnosis [35][36][37], we have normalized the number of all-listed ADHD hospital discharges to a percentage of total discharges for all-listed mental disorders recorded in HCUPNET.…”
Section: Hospitalization Datamentioning
confidence: 99%
“…2,3 Effective treatment of ADHD improves symptoms, emotional lability, and patient functioning. 4 While Paris et al's main concern is overtreatment of ADHD, we believe the risks of missed diagnosis and undertreatment, are far more compelling.…”
Section: Dear Editormentioning
confidence: 99%